Can adnexal torsion be predicted by measuring plasma heat shock protein 70 level? An experimental study - Cilgin, Hasan; Simsek, Mehmet; Bal, Ramazan (Springer Heidelberg, 2017)
Objective To investigate the effect of adnexal torsion on the plasma heat shock protein 70 level and to determine whether plasma heat shock protein 70 can be used in the adnexal torsion diagnosis. Materials and methods Twenty-one nulligravid 3-monthold female Wistar albino rats were randomly and equally allocated into three groups: study group (ovarian torsion) (n = 7), laparotomy group (sham operation) (n = 7) and control group (received no special treatment) (n = 7). Ovarian torsion model was created by twisting the right adnexa two times around its pedicle and fixing over the lateral pelvis with 6.0 polyglactin absorbable surgical suture. Blood was sampled before and 12 h after operation to assess plasma heat shock protein 70 level. Results In the study group, the mean plasma heat shock protein 70 level was significantly higher than that in the laparotomy and control groups (1.75 +/- 0.25), (1.16 +/- 0.99), (1.19 +/- 0.11) ng/ml, respectively, P = 0.001), following 12 h of ovarian torsion. Conclusion A significant increase in plasma heat shock protein 70 level in the study group indicates that plasma heat shock protein 70 level could be used as a serum marker in the early detection of adnexal torsion. However, further clinical and experimental studies of a larger size are required.
Keywords: Adnexal torsion; Heat shock protein 70; Ischemia